Peningkatan Kemampuan Berbahasa Krama Inggil Anak Usia 5-6 Tahun Melalui Metode Bermain Peran di TK Pertiwi Parakan - Fatatun Malihah; Risdianto Hermawan (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
The ability to use Javanese krama inggil in early childhood plays an important role in developing polite character and preserving local culture. However, research findings at Pertiwi Parakan Kindergarten indicate that most children aged five to six years are not yet able to use krama inggil appropriately in daily communication. This study aims to improve children's ability to use Javanese krama through the role-playing method. The research employed a Classroom Action Research approach conducted in three cycles. Data were collected through observation and analyzed using descriptive quantitative methods based on the percentage of learning mastery. The results show a gradual improvement in language ability, with learning mastery reaching 85 percent in the third cycle. These findings indicate that the role-playing method is effective in improving children's ability to use Javanese krama and supports the development of polite character in early childhood. The implication of this study suggests that role-playing is a vital pedagogical tool for internalizing cultural values and polite character in early childhood. It is recommended that teachers integrate traditional language learning through interactive play-based methods and that further research explore its long-term impact on children's social interaction